Penggunaan Media Tangram Dalam Mengenalkan Bentuk Geometri Pada Kelompok A Di Tk Islam Terpadu Wildani ( Studi Kasus) - Zunita, Nur; Arif, Muchamad (MOTORIC, 2024)
ABSTRACT This research focuses on improving early childhood cognitive abilities in recognizing geometric shapes through a tangram media approach. Conducted at the Faculty of Education, Narotama University Surabaya, this case study research involved three participants aged 4-5 years. Qualitative research methods were used with observation, interview, and documentation techniques. The results show that the use of tangram media in learning effectively improves children's understanding of geometric shapes. The practical implication is the need for collaboration between teachers and parents in helping children's cognitive development through this approach. This research has the potential to enrich early childhood education strategies with the tangram media approach. Keywords: geometric shapes, tangrams, early childhood.